Dental and oral health assessments in the German National Cohort (NAKO) - Stefanie Samietz; Katrin Borof; Katrin Hertrampf; Ghazal Aarabi; Antonio Ciardo; Hannah Finke; Daniel Hagenfeld; Jan Kühnisch; Maurice Rütters; Sebastian-Edgar Baumeister; Stefan Lars Reckelkamm; Ti-Sun Kim; et al. (BMC Oral Health, 2025)
Abstract Background Despite considerable improvements in oral health in recent decades, caries and periodontitis are still widespread, ranking among the most prevalent diseases worldwide and requiring future research. The German National Cohort (NAKO Gesundheitsstudie, NAKO) is a large-scaled, multidisciplinary, nationwide, multi-centre, population-based, prospective cohort study with oral examinations that aims to provide a resource to study risk factors for major diseases. The aim of the present article is to provide the methodological background, to report on the data quality, and to present initial results of the oral examinations. Methods During baseline examinations (2014–2019), a total of 205,184 persons aged 19–74 years has been examined in 18 study centres, including, among others, a dental interview, stimulated saliva sampling, and recording of the numbers of present teeth and prostheses (standard Level 1 program). As part of the Level 2 program that was offered to 20% randomly selected participants, each study centre selected one of three modules, one of them being the Level 2 oral examination. This extended program was carried out in a subgroup of 20,828 participants, including collection of detailed information on the dental and prosthetic status as well as on periodontal, cariological and functional aspects. To ensure reliability and reproducibility, study nurses were trained and calibrated by dental experts. In addition, a reliability study was conducted among 794 Level 1 and 359 Level 2 participants, reporting intra class correlation and kappa coefficients. Results Intra class correlation and kappa coefficients for observer agreement and reliability were consistently above 0.7, indicating good to excellent reliability of all dental measurements. For example, intra class correlation was 0.937 for the number of present teeth (Level 1), 0.740 for mean probing depth (PD) and 0.797 for active mouth opening. An initial inspection of the data showed that the median number of present teeth was 27, of which on average 6.9 teeth were healthy and caries-free. Average mean PD was 1.92 mm. An orthodontic treatment was reported by 35.5% of participants. Discussion Overall, the dental study protocol was feasible and successfully integrated into the NAKO’s overall assessment program. However, rigorous support of the study centres by dental professionals was required to ensure high quality data. In summary, high-quality data collection within the NAKO pave the way for future investigation of potential risk factors for oral diseases and links between oral and systemic diseases and conditions.